Potential of Plant Bioactive Compounds as SARS-CoV-2 Main Protease (Mpro) and Spike (S) Glycoprotein Inhibitors: A Molecular Docking Study. (23rd December 2020) - Tallei, Trina Ekawati; Tumilaar, Sefren Geiner; Niode, Nurdjannah Jane; Fatimawali; Kepel, Billy Johnson; Idroes, Rinaldi; Effendi, Yunus; Sakib, Shahenur Alam; Emran, Talha Bin
Abstract : Since the outbreak of the COVID-19 (coronavirus disease 19) pandemic, researchers have been trying to investigate several active compounds found in plants that have the potential to inhibit the proliferation of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2). The present study aimed to evaluate bioactive compounds found in plants using a molecular docking approach to inhibit the main protease (M pro ) and spike (S) glycoprotein of SARS-CoV-2. The evaluation was performed on the docking scores calculated using AutoDock Vina (AV) as a docking engine. A rule of five (Ro5) was calculated to determine whether a compound meets the criteria as an active drug orally in humans. The determination of the docking score was performed by selecting the best conformation of the protein-ligand complex that had the highest affinity (most negative Gibbs' free energy of binding/Δ G ). As a comparison, nelfinavir (an antiretroviral drug), chloroquine, and hydroxychloroquine sulfate (antimalarial drugs recommended by the FDA as emergency drugs) were used. The results showed that hesperidin, nabiximols, pectolinarin, epigallocatechin gallate, and rhoifolin had better poses than nelfinavir, chloroquine, and hydroxychloroquine sulfate as spike glycoprotein inhibitors. Hesperidin, rhoifolin, pectolinarin, and nabiximols had about the same pose as nelfinavir but were better than chloroquine and hydroxychloroquine sulfate as M pro inhibitors. This finding implied that several natural compounds of plants evaluated in this study showed better binding free energy compared to nelfinavir, chloroquine, and hydroxychloroquine sulfate, which so far are recommended in the treatment of COVID-19. From quantum chemical DFT calculations, the ascending order of chemical reactivity of selected compounds was pectolinarin > hesperidin > rhoifolin > morin > epigallocatechin gallate. All isolated compounds' C=O regions are preferable for an electrophilic attack, and O-H regions are suitable for a nucleophilic attack. Furthermore, Homo-Lumo and global descriptor values indicated a satisfactory remarkable profile for the selected compounds. As judged by the RO5 and previous study by others, the compounds kaempferol, herbacetin, eugenol, and 6-shogaol have good oral bioavailability, so they are also seen as promising candidates for the development of drugs to treat infections caused by SARS-CoV-2. The present study identified plant-based compounds that can be further investigated in vitro and in vivo as lead compounds against SARS-CoV-2.